Three new species of cockroach genus Hemithyrsocera Saussure, 1893 (Blattodea: Ectobiidae: Blattellinae) with redescriptions of two known species from China - Wang, Zongqing; Che, Yanli (Zootaxa, 2017)
This paper deals with five species of the genus Hemithyrsocera Saussure, 1893, of which three new species, H. forcipata, H. spinibarbis and H. longiseta spp. nov., are described and illustrated, H. banvaneuensis (Roth, 1985) is reported for the first time from China, plus one little known species H. simulans (Bey-Bienko, 1969) are redescribed and illustrated. A key to all Chinese species of Hemithyrsocera is provided.